The Influence of Different Irrigation Scenarios on the Yield and Sustainability of Wheat Fodder under Hydroponic Conditions - Andrius Grigas; Dainius Savickas; Dainius Steponavičius; Žygimantas Niekis; Jonas Balčiūnas (Agronomy, 2023)
Agriculture uses more water than any other resource to produce animal feed and wastes much of it through inefficiency. One possible alternative to solve this problem is hydroponically grown animal fodder, which under hydroponic conditions can achieve optimal results and, most importantly, use expensive resources, such as water, more efficiently. In the conducted research, different irrigation scenarios (IR1–IR6) were investigated when the water flow rate, irrigation frequency, and duration (IR1—1 l min−1, 4 times day−1, 120 s; IR2—2 l min−1, 4 times day−1, 120 s; IR3—3 l min−1, 4 times day−1, 120 s; IR4—1 l min−1, 8 times day−1, 60 s; IR5—2 l min−1, 8 times day−1, 60 s; and IR6—3 l min−1, 8 times day−1, 60 s) were changed during the hydroponic wheat fodder cultivation using a 7-day growth cycle. The results showed that the highest yield from the used seed was obtained in scenarios IR5 (5.95 ± 0.14 kg kg−1) and IR6 (5.91 ± 0.19 kg kg−1). In terms of frequency and irrigation duration, in IR1, IR2, and IR3, the average yield reached 4.7 ± 1.85 kg kg−1, and in scenarios IR4, IR5, and IR6, the average yield was 15.4% higher—5.55 ± 1.63 kg kg−1. The results obtained showed that by increasing the flow rate (from 1 l min−1 to 3 l min−1) and the frequency of irrigation (from 4 times day−1 to 8 times day−1), the yield increased by 32.5%, but the mass of the grown fodder per liter of water used simultaneously decreased by 50.6%. The life cycle assessment showed that although irrigation scenario IR4 had the most efficient use of water, the CO2 footprint per functional unit (FU) was the highest due to the lowest yield compared to the other five irrigation scenarios. The lowest environmental impacts per FU were obtained in scenarios IR5 and IR6 (100.5 ± 3.3 and 100.6 ± 2.4 kg CO2eq t−1, respectively).